Averting Apocalypse at Rajneeshpuram - Goldman, Marion S. (Sociology of religion, 2009)
From 1981 to 1986, most outsiders foretold bloodshed at Rajneeshpuram, the communal city in central Oregon that was built around an Indian charismatic leader, Bhagwan Shree Rajneesh (later known as Osho). However, violence never escalated to the point of mass murder, suicides, or large, collective attacks. The Rajneesh case provides a fruitful context to explore the question: How is large-scale collective violence in new religions averted? The case of Rajneeshpuram foregrounds three factors that were most important to relatively peaceful resolution of a situation fraught with danger: life-embracing doctrine, devotees' continued contact with networks outside Rajneeshpuram, and law enforcement committed to due process. Each of these influenced outcomes at different stages of tension between the group and the surrounding community. Close consideration of this case provides a framework to examine other alternative religious groups that have exploded in large-scale collective violence or appear to have the potential to do so.